The effects of palm vitamin E supplementation on Glycemic Control and Lipid Profile in Streptozotocin-Induced Diabetic Rats - Siti Balkis Budin; Abdul Gapor Mohd Top; Wan Nzaimoon Wan Mohamud; Mokhtar Abu Bakar; Khairul Osman; Monica Yau Swee Eng; Jamaludin Mohamed (penerbit ukm, 2005)
In this study, the effects of palm vitamin E (PV) supplementation on glycemic control and lipid profile in diabetic-induce Sprague-Dawley rats have been evaluated. Diabetes in the rats was induced by a single intravenous streptozotocin (50 mg/kg body weight). The diabetic rats were divided into two groups; supplemented with 200 mg/kg body weight/day of PV and non-supplemented with PV (No PV group). Non-diabetic rats (NDM) formed the control group and only received saline injection. After eight weeks of daily supplementation, PV significantly lowered the fasting blood glucose (FBG) and glycosylated haemoglobin (HbA1c) levels (p<0.01) as compared with No PV group.However, these levels were still significantly higher than the control group (p<0.001). PVsupplementation group also showed significantly lower levels of plasma total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) (p<0.001) and higher level of highdensity lipoprotein cholesterol (HDL-C) (p<0.001) as compared with No PV group. In conclusion, this study suggested that PV may be effective in controlling glycemic status and improving dyslipidemia in streptozotocin-induced diabetic rats and has the potential in reducing cardiovascular complication due to diabetes mellitus.